Graves’ disease with hyperfunctioning thyroid nodule harboring thyroid carcinoma. Case report and literature review - A. A. Kuprin; V. Y. Malyuga; I. V. Makedonskaya; A. A. Melnikova (Опухоли головы и шеи)
According to the American Thyroid Association’s 2015 guidelines: “Since hyperfunctioning nodules rarely harbor malignancy, if one is found that corresponds to the nodule in question, no cytologic evaluation is necessary”. These findings are based on numerous studies proving the rareness of the combination of functional autonomy and thyroid cancer, and when such casuistry is detected, the non-aggressive course of the malignant process is observed.Rare revealing of malignant nodules functional autonomy can be attributed to several fundamental bases of non-medullary thyroid carcinoma pathogenesis. According to one of the hypotheses of carcinogenesis, dedifferentiation of thyrocytes occurs initially with the loss of the possibility of the sodium-iodine symporter synthesis, and later of the thyroid-stimulating hormone receptor synthesis by the cell, which reduces the hormone production by tumor cells. In addition, hyperthyroidism has a protective feature. It reduces the level of thyroid-stimulating hormone (which causes hypertrophy, hyperplasia of thyrocytes and has an antiapoptotic effect). This protective function is used in practice for suppressive therapy in the postoperative period, which reduces the progression, recurrence and mortality from thyroid cancer. The above circumstances prove the rareness of the clinical observation described below, which deserves additional attention and subsequent discussion.